AD interdisciplinary architecture [edited by] Nicoletta Trasi. - Trasi, Nicoletta. (John Wiley & Sons, 2001)
Takes a holistic view of the design of our environment, covering historical precedents, contemporary developments, and possible future trends. * Comprehensively illustrated with many lavish photographs, as well as plans and drawings. * Material draws information from cutting-edge articles and ideas.